MEMBANGUN BUDAYA HUKUM PANCASILA SEBAGAI BAGIAN DARI SISTEM HUKUM NASIONAL INDONESIA DI ABAD 21 - Hartono, Sunaryati (Veritas et Justitia, 2015)
This article discusses the weaknesses of Indonesian (internal) legal culture. The author argues that this weakness points to the attitudes, behavior, and beliefs about the proper place of law in daily life as entertained by individuals working in the government, law making institutions as well as those working in the law enforcement sector. Moreover, this internal weakness in Indonesian legal culture, poses a threat to the unity of Indonesia as a nation. One solution offered is to return to and revive the State ideology and philosophy, Pancasila, as the basis to develop a more viable and healthy Indonesian legal culture.